ANALISIS HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JUAL BELI PADA PRODUK BAI’ AL-WAFA’ DI BMT UGT SIDOGIRI CABANG BULAK RUKEM SURABAYA - muchlis muchlis; Dian Berkah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2019)
ABSTRACTThe thesis entitled "Legal Analysis of Islamic Economics on the Practice of Buying and Selling at Bai 'Al-Wafa' Products in Bmt Ugt Sidogiri, Bulak Rukem Branch Surabaya, is motivated by the customer's need for money so that customers sell their valuables to BMT UGT Sidogiri to get money but in the sales process there is an agreement that the goods purchased by BMT UGT Sidogiri will be bought back at a certain time according to the agreement, there will be a sale and purchase contract for 'wafa'. This study aims to analyze the selling procedures for buying and selling procedures for bai 'al-wafa' products at BMT UGT Sidogiri, Surabaya Bulak Rukem branch and for analyzing problems regarding Sharia Economic Legal Analysis on the practice of buying and selling on bai 'al-wafa' products at BMT UGT Sidogiri, Bulak Rukem Surabaya branch.The research method used in this study is a qualitative field research method, which is sourced from research informants obtained at the time of conducting research at Jokotole Pamekasan Syariah Pawnshop and supported by data that can be strengthened by literature as a supporter. This research is descriptive qualitative, using data collection techniques through interviews, observation, and documentation. The approach used is juridical sociology which is then analyzed using inductive thinking patterns.Based on the results of research in the field related to Sharia Economic Legal Analysis of the practice of buying and selling on bai 'al-wafa' products at BMT UGT Sidogiri, Surabaya's Bulak Rukem branch was preceded by a survey process by BMT UGT Sidogiri to customers to ensure the feasibility of using bai 'wafa products 'Then after getting the agreement, the customer submits several requirements for' wafa 'who are asked to be able to sell their valuables to get money. The BMT UGT Sidogiri calculates ujrah costs because the items they buy will be rented back to customers some time until customers can buy back the valuables that they have sold to BMT UGT Sidogiri, Bulak Rukem Branch, Surabaya. the practice of buying and selling on bai 'al-wafa' products in BMT UGT Sidogiri, Bulak Rukem Surabaya branch, the procedure is in accordance with Islamic law both described in the Qur'an, hadith, muamalah fiqh, KHES and DSN-MUI fatwa. However, in the process of handing over the goods in contradiction with Al-in'iqad and Article 76 KHES in terms of the delivery of goods because the goods sold by customers do not exist in the contract peri Key Word : Islamic Economics, Practice of Buying and Selling, Bai 'Al-Wafa'.